Show Boat - Sidney, George (Warner Home Video, 2003)
From St. Louis to Natchez to New Orleans. And from novel (by Edna Ferber) to Broadway smash (by Jerome Kern and Oscar Hammerstein II) to three film version (1929, 1936, 1951) to stage revivals. Like Or Man River, Show Boat just keeps rollin' along. This gleaming 1951 version of the melodious favorite has it all: glorious stars in Technicolor radiance, a made - from - scratch 170 -foot paddle - wheeler, the savvy of Arthur Freed's production unit and director George Sidney, timeless songs and an equally timeless outcry against racial bigotry. Kathryn Grayson, Ava Gardner and Howard Keel headline this saga of riverboat lives and loves featuring Make believe, Can't Help Lovin' Dat Man, Bill and more evergreens. "This was music that would outlast Kern's day and mine." Feber said in recalling her first reaction to hearing Or Man River, She was right as rain.